ANTECEDENT ONLINE PURCHASE INTENTION ON SOCIAL MEDIA - Sri Lestari; Diandra Vizara Santoso; Julio Benedick; Ayu Eka Sari (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to identify the factors that influence online purchase intentions on social media. To that end, the authors developed a framework that describes the relationship between information credibility, information usefulness, attitude towards information, information adoption, and online purchase intentions. This research was conducted through an online survey involving 251 respondents from various backgrounds. The data obtained were analyzed using a structural equation model (SEM). The results showed that information credibility has a significant direct influence on consumer attitudes, which in turn influence online purchase intentions. Nonetheless, the findings also reveal that the usefulness of information does not have a significant effect on consumers' decision to adopt the information. The survey mainly involved young consumers, so the generalizability of the results to other age groups may be limited. For practitioners, the findings emphasize the importance of information credibility in increasing online purchase intentions, given that information that is perceived as credible can increase consumer confidence in making transactions.